Exposing Nipah virus: an epidemiological study of another thread in Kerala, South India - Prakash, Kartikay; Yadav, Reetu; Tiwari, Shashank (International Journal of Research in Medical Sciences, 2024)
Bats spread the Nipah virus, which causes severe encephalitis and high mortality. Multiple reports have come from Malaysia, Bangladesh, Singapore, and India. Pteropus fruit bats are known to host the virus. The virus has caused four outbreaks in Kerala in the past quinquennium. Scholars believe the virus is indigenous to the state's bat population. Climate change, resource depletion, deforestation, natural terrain changes, farming, and industrialization all contribute to viral disease outbreaks. In this review, we will discuss the epidemiological background of the previous NiV outbreak. We will also examine the transmission method epidemic prevention and control strategies and possible causes of the outbreak. Four Nipah epidemics have occurred in Kerala in the past five years. Expert investigation suggests that the virus may be endemic in the state’s bat population. Kerala, India, has many bat species. In 2018, research found viral infections in the local fruit bat population. Traditionally, people eat fresh toddy or sap from trees, which can be polluted by bats carrying the Nipah virus. Kerala's healthcare system also closely monitors unexplained fevers for Nipah virus infections. The World Health Organisation and Indian Council of Medical Research found that the entire state is susceptible to Nipah virus infections. The virus is a major cause of encephalitis outbreaks, which have high mortality rates, mostly in Indo-Bangladesh.